2019
DOI: 10.3390/tropicalmed4010030
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Schistosomiasis Mekongi from Endemic Areas in Cambodia and the Lao People’s Democratic Republic: Current Status and Plans

Abstract: The areas endemic for schistosomiasis in the Lao People's Democratic Republic and in Cambodia were first reported 50 and 60 years ago, respectively. However, the causative parasite Schistosoma mekongi was not recognized as a separate species until 1978. The infection is distributed along a limited part of the Mekong River, regulated by the focal distribution of the intermediate snail host Neotricula aperta. Although more sensitive diagnostics imply a higher figure, the current use of stool examinations suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
1
41
1
Order By: Relevance
“…Key informants emphasized that community involvement in the planning and implementation of interventions is crucial to ensure uptake, acceptance and sustainability of WASH interventions. Successful examples of comprehensive community-led MDA combined with community-led WASH (CL-WASH) interventions for schistosomiasis control in Cambodia and Lao PDR have been published [ 24 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Key informants emphasized that community involvement in the planning and implementation of interventions is crucial to ensure uptake, acceptance and sustainability of WASH interventions. Successful examples of comprehensive community-led MDA combined with community-led WASH (CL-WASH) interventions for schistosomiasis control in Cambodia and Lao PDR have been published [ 24 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several key informants pointed out that early childhood education has proven effective in adapting and improving WASH behavior and is applied for trachoma and soil-transmitted helminth (STH) control and prevention through habit formation. Community participation was identified by key informants and in the literature as crucial to maximize acceptance, gain a sense of ownership and empowerment and achieve sustainability of interventions and activities including vector control, WASH, surveillance, treatment, health education and behavior change communication in programmes targeting malaria, dengue, schistosomiasis, Guinea worm and other parasitic and vector-borne diseases [ 11 , 24 , 43 , 46 , 53 , 60 62 , 72 76 ]. Caregivers, social groups, religious or community leaders, teachers and health staff should be engaged in control activities, intervention planning and design of tools [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, evidence demonstrating the ability of MDA to control the transmission of schistosomiasis in high prevalence areas is mixed, in part because the impact of MDA will vary across different epidemiological settings. There are many regions, such as the Mekong River in Cambodia, where excellent progress has been made, with heavy-intensity infections reduced to below 1% [5, 6]. However, several recent studies in Africa have demonstrated limited progress in reducing prevalence in localized high-transmission areas, despite high MDA coverage [79].…”
Section: Introductionmentioning
confidence: 99%